The influence of turpentine additive on the ecological parameters of diesel engines - Butkus, Algis; Pukalskas, Saugirdas; Bogdanovičius, Zenonas (Transport, 2007)
After Lithuania's accession to the EU it is very important to use a larger amount of renewable fuel. Based on economic and environmental considerations in Lithuania, we are interested in studying the effects of turpentine contents in the blended turpentine‐diesel fuel on the engine performance and pollutant emission of compression ignition (CI) engine. Therefore, we used engine test facilities to investigate the effects on the engine performance and pollutant emission of 5 % turpentine in the fuel blend. The tests were carried out in the laboratory on an engine dynamometer of the car Audi 1Z and tractor D21 diesel engines. The experimental results showed that turpentine used in the fuel blend for these diesel engines had a positive influence on the engine performance and exhaust emission.First Published Online: 27 Oct 2010